2019
DOI: 10.1007/s12265-019-09939-5
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Pathways of Testosterone: Clinical Implications

Abstract: Cardiovascular diseases (CVD) are one of the leading causes of death worldwide. Testosterone (T) is an important sex hormone that triggers several genomic and non-genomic pathways, leading to improvements of several cardiovascular risk factors and quality of life in men. At the vascular level, the key effect of T is the vasorelaxation. This review discusses the molecular pathways and clinical implications of T in the vascular system. Firstly, the mechanisms involved in the T vasodilator effect will be presente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
15
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 169 publications
(279 reference statements)
2
15
0
4
Order By: Relevance
“…In addition, we also found that the level of 11-ketoetiocholanolone, an endogenous anabolic androgenic steroid, increased after GXSTC treatment. Studies have shown that lower levels of serum endogenous testosterone are associated with a higher risk of diseases such as atherosclerosis, myocardial infarction, chronic heart failure and obesity (Fink et al, 2018;Lorigo et al, 2020), and our results indicated that GXSTC also played a role in the regulation of androgen metabolism.…”
Section: Discussionsupporting
confidence: 67%
“…In addition, we also found that the level of 11-ketoetiocholanolone, an endogenous anabolic androgenic steroid, increased after GXSTC treatment. Studies have shown that lower levels of serum endogenous testosterone are associated with a higher risk of diseases such as atherosclerosis, myocardial infarction, chronic heart failure and obesity (Fink et al, 2018;Lorigo et al, 2020), and our results indicated that GXSTC also played a role in the regulation of androgen metabolism.…”
Section: Discussionsupporting
confidence: 67%
“…The following hypothesis may explain our results: the altered testosterone-induced relaxation and still unchanged nuclear AR expression may suggest the involvement of 'membrane-bound or other' receptors, signal transduction pathways, and ion channels in the identified functional damage. Additionally, it is probable that both endotheliumdependent and endothelium-independent, direct vascular smooth muscle cell activation pathways are present [18], but the exact mechanisms and the detailed cardiovascular effects of androgens are still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Sexual steroids have potential roles in cardiovascular sex-related variance; testosterone (T) and 17-β-estradiol (E2) are the two most potent sexual steroids (T in men and E2 in women), and both can cause genomic and rapid, non-genomic vasodilation via several different mechanisms and pathways, mostly in the appropriate sex [17,18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lorigo et al summarized the association of testosterone with multiple risk factors of CVDs, such as type 2 diabetes mellitus, obesity, hypertension, and dyslipidemia. The relationship between the reduced testosterone level and the pathophysiology of vascular dysfunction, coronary arterial diseases, heart failure, ischemic stroke, and atrial fibrillation has also been discussed [5]. These papers provide a very good overview to enhance our knowledge of gender differences in CVDs.…”
mentioning
confidence: 99%